Systemic Decision Making Fundamentals for Addressing Problems and Messes - Hester, Patrick T.; Adams, Kevin MacG.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This expanded second edition of the 2014 textbook features dedicated sections on action and observation, so that the reader can combine the use of the developed theoretical basis with practical guidelines for deployment. It also includes a focus on selection and use of a dedicated modeling paradigm - fuzzy cognitive mapping - to facilitate use of the proposed multi-methodology. The end goal of the text is a holistic, interdisciplinary approach to structuring and assessing complex problems, including a dedicated discussion of thinking, acting, and observing complex problems. The multi-methodology developed is scientifically grounded in systems theory and its accompanying principles, while the process emphasizes the nonlinear nature of all complex problem-solving endeavors. The authors' clear and consistent chapter structure facilitates the book's use in the classroom.
Part I: A Frame of Reference for Systemic Decision Making -- Chapter 1.Introduction -- Chapter 2. Problems and Messes -- Chapter 3. Systemic Thinking -- Chapter 4. Systems Theory -- Chapter 5. Complex Systems Modeling -- Part II: Thinking Systemically -- Chapter 6. The Who of Systemic Thinking -- Chapter 7. The What of Systemic Thinking -- Chapter 8. The Why of Systemic Thinking -- Chapter 9. The Where of Systemic Thinking -- Chapter 10. The How of Systemic Thinking -- Chapter 11. The When of Systemic Thinking -- Part III: Acting Systemically -- Chapter 12. Systemic Action -- Chapter 13. Anatomy of a Decision -- Chapter 14. Decision Implementation -- Part IV: Observing Systemically -- Chapter 15. Observation -- Chapter 16. Systemic Learning -- Chapter 17. Ford Pinto Case Study -- Chapter 18. Conclusion.
Keywords: Dynamics; Nonlinear theories; System theory; Control theory; Operations research; Management science; Applied Dynamical Systems; Systems Theory, Control; Operations Research and Decision Theory; Operations Research, Management Science